Cost‐Effective Sediment Dredge Disposal Options for Small Craft Harbors in Canada. Issue 4 (17th September 2013) - Walker, Tony R.; MacLean, Bradley; Appleton, Rebecca; McMillan, Scott; Miles, Mary
Abstract Sediment dredge disposal options were reviewed to improve cost‐effectiveness and environmental safety for dredging of coastal sediments at the Department of Fisheries and Oceans Small Craft Harbours (DFO‐SCH) program in Canada. Historically, contaminated dredge sediments exceeding federal guidelines were disposed of in nearby landfills. Recent federal regulatory changes in sediment quality guidelines adopted by provincial regulators in Canada has resulted in updates to guidelines for disposal of contaminated solids in landfills. Updates now require specific and general disposal options for contaminated dredge material destined for land‐based disposal, resulting in more expensive disposal in containment cells (if contaminated sediments exceed federal guidelines). However, as part of this study, a leachate testing method was applied to contaminated sediments to simulate migration of potential contaminants in groundwater. Using this approach, leachate quality was compared to federal freshwater criteria and drinking water quality guidelines for compliance with new regulations. Leachate testing performed on the highest sediment contaminant concentrations triggered less than 2 percent potable water exceedances, meaning that most dredge spoils could be disposed of in privately owned or provincially operated landfill sites, providing less expensive disposal options compared to containment cell disposal. Current dredge disposal practices were reviewed at 35 harbor sites across Nova Scotia and their limitations identified in a gap analysis. Improved site management was developed following this review and consultation with interested marine stakeholders. New disposal options and chemical analyses were proposed, along with improvements to cost efficiencies for management of dredged marine sediments in Atlantic Canada. © 2013 Wiley Periodicals, Inc.